Assessment of the Role of Small-Scale Irrigation Practice on House Hold Food Security in Haramaya District, Eastern Haraghe Zone, Eastern Ethiopia - Tasisa Temesgen Tolossa (Turkish Journal of Agriculture: Food Science and Technology, 2020)
However, irrigation practice is poor in Ethiopia, increases agricultural production and productivity. The study was conducted in Haramaya district, Eastern Ethiopia. The object of this study is to see contribution of small scale irrigation towards increasing agricultural production, and identify the factors that affecting the use of small scale irrigation. From the district, three peasant associations were purposively selected each from different agro ecological classifications. Sampling size of 116 households was interviewed and Secondary data were also collected from the office. Three different types of irrigation were identified; Surface irrigation type using furrow method of irrigation is the most common irrigation type in the study area, which accounts about 66.5%. The study indicated that, water scarcity, lack improved seed, and disease outbreak and drought were among the major constraints of irrigation practices in the study area. Therefore practicing water harvesting and supplying improved technologies provide extended service regularly for farmers should be practiced in the future.